Defesa Civil do município de São Paulo: desafios à articulação e relações institucionais - Jaroszewski, Cassiane da Rocha (2013)
The objective of this work is to analyze the current civil defense institutional arrangement for the municipality of São Paulo, in which the entities responsible for formulating and carrying out such a complex policy belong to two distinct municipal secretaries (SMSU and SMSP). From bibliographical revision, interviews and fieldwork, we intend to show how such an institutional arrangement is viewed by professionals who are involved with the civil defense of São Paulo. In order to reach this goal, we have undertaken a historical analysis of civil defense policy in both national and municipal scope. In addition to the diagnostic of the current situation, this dissertation aims to discuss alternative institutional arrangements for the organization of civil defense public policy. Finally, we intend to propose measures for incremental improvements in the civil defense of the city, so that it may fully fulfill its responsibility of emergency and disaster risk management.